Reviews (New blackfriars, 1966)
STUDIES IN CHRISTIAN EXISTENTIALISM by John Macquarrie OLD AND NEW IN INTERPRETATION by James Barr JOACHIM JEREMIAS. THE EUCHARISTIC WORDS OF JESUS. Translated by Norman Perrin A NEWMAN COMPANION TO THE GOSPELS, by Armel J. Coupet EDITH STEIN, by Jean de Fabregues. Translated from the French by Donald M. Antoine PASCAL by Jean Steinmann, translated by Martin Turnell. Burns & Oates PASCAL, by J. H. Broome. Edward Arnold PASCAL by Jean Mesnard. (“Les Ecrivains devant Dieu”, Desc/6e de Brouwer GILBERT FOLIOT AND HIS LETTERS by Dom Adrian Morey and C. N, L Brooke ALAN DE LILLE. TEXTES INEDITS. AVEC UNE INTRODUCTION SUR SA VIE ET SES OEUVRES REFORM AND REACTION: THE POLITICO-RELIGIOUS BACKGROUND OF THE SPANISH CIVIL WAR. by Jose M. Sanchez THE SPANISH INQUISITION by Henry Kamen. Weidenfeld and Nicolson SCIENCE. MAN AND MORALS by W. H. Thorpe, F.R.S. Methuen IS CELIBACY OUTDATED? by Ida Gorres